Government Expenditure and Economic Growth Nexus in Mena Countries: Frequency Domain Spectral Causality Analysis - Ayad, Hicham (Economics and Business, 2020)
The paper aims at examining the causal relationship between economic growth and government expenditure in selected MENA countries over the period of 1987–2017. Unlike previous studies, we examine the causality in both panel data and time series data to get a clear idea about the causal relationships individually and as a full sample. We also revisited the causal relationship between the two variables within the framework of frequency domain causality. Our findings support the neutrality hypotheses in the short-run term for most of the countries. Thus, economic growth and government expenditure at most frequency levels evolve independently. On the other hand, we found the support of Wagner’s law, Keynes view, neutrality and bidirectional hypotheses in the long term.